INTEGRATION OF MAQASHID SYARIAH VALUES IN RISK BASED DECISION MAKING: A CASE STUDY OF CV. UTAMA MAJU BERSAMA - Anam, Rizqy Khairul; Purwanto, Purwanto; Rifai, Fuad Yanuar Akhmad (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study aims to analyze how Maqashid Syariah values are integrated into risk-based decision making in a construction services company, using the case of CV. Utama Maju Bersama. The company faces technical risks such as well-drilling failures, occupational safety hazards, and clients’ financial challenges. The research uses a descriptive qualitative method, collecting data through in-depth interviews with the director and manager, as well as company documentation.The results show that although the management does not formally recognize the term Maqashid Syariah, its principles are substantially implemented in decision making. The value of hifz al-nafs is reflected in the use of PPE and workplace safety procedures; hifz al-maal in clear work contracts, interest-free installment payment schemes, and an internal cooperative; hifz ad-din in worship reminders and flexible prayer times; and hifz an-nasl in prioritizing the recruitment of married workers and providing social assistance. In addition, risk decisions are made through mutual consultation (musyawarah) with clients to achieve fair agreements, avoid gharar (uncertainty), and maintain customer satisfaction. These findings demonstrate that integrating Maqashid Syariah values can serve as an ethical and strategic approach to risk management in construction service companies, supporting business sustainability, social justice, and shared prosperity.